Infantile hemangioma of the upper eyelid in one very and two extremely preterm infants: INFANTILNI HEMANGIOMI KAPKA - Žeravica, Milica; Matić, Aleksandra; Matić, Milan; Pajić, Miloš; Prćić, Sonja (Vojnosanitetski pregled, 2023)
Introduction. Infantile hemangiomas (IHs) are the most common vascular tumors of infancy whose frequency increases with decreasing gestational age. Although rare, periorbital IHs (PIHs) have a high complication rate, with a substantial risk of impaired vision and aesthetic consequences. Because they are considered high-risk IH, such patients must be treated. In the available literature, there is little information about the treatment of IHs in very and extremely preterm newborns and infants. Case report. We present three male infants (one very and two extremely prematurely born) with PIHs involving the upper eyelid. In all three cases, IHs were solitary but with different subtypes according to soft-tissue depth (superficial, combined, deep). No additional congenital anomalies were found in any of these cases. An individualized approach to the management of each patient was applied. All infants were treated with oral administration of propranolol, with careful monitoring for potential side effects of the drug and adjustment of treatment, following their eventual occurrence. The introduction of oral propranolol was carried out in a hospital setting, with a gradual increase of the drug dose until the target dose was reached. Conclusion. In the case of PIH, an ophthalmologist is an inevitable part of the medical team. Very and extremely preterm infants are already under the supervision of an ophthalmologist due to mandatory screening for retinopathy of prematurity; however, if they also have PIHs, monitoring must be particularly detailed and long-lasting.
Keywords: drug therapy; eyelids; hemangioma; infant, extremely premature; infant, premature; propranolol